2013
DOI: 10.1167/iovs.13-12439
|View full text |Cite
|
Sign up to set email alerts
|

Bleb Analysis by Using Anterior Segment Optical Coherence Tomography in Two Different Methods of Trabeculectomy

Abstract: Citation: Hamanaka T, Omata T, Sekimoto S, Sugiyama T, Fujikoshi Y. Bleb analysis by using anterior segment optical coherence tomography in two different methods of trabeculectomy. Invest Ophthalmol Vis Sci. 2013;54:6536-6541. DOI: 10.1167/iovs.13-12439 PURPOSE. To investigate the correlation between bleb morphology and IOP control via the modified Indiana Bleb Appearance Grading Scale (IBAGS) and anterior-segment optical coherence tomography (AS-OCT) in two different trabeculectomy (TLE) groups.METHODS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 16 publications
2
48
0
1
Order By: Relevance
“…When calculating the correlation coefficients for IBAGS scores and final IOP at 3 months, we found that horizontal extent and vascularity were negatively correlated for both surgical groups (À0.74 and À0.46, respectively), meaning the broader and more vascular the bleb, the lower the IOP. In the study by Hamanaka et al, 19 they found that a wider bleb extent and leak showed success in IOP in limbal-based TRAB with no significant results for fornix-based TRAB.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…When calculating the correlation coefficients for IBAGS scores and final IOP at 3 months, we found that horizontal extent and vascularity were negatively correlated for both surgical groups (À0.74 and À0.46, respectively), meaning the broader and more vascular the bleb, the lower the IOP. In the study by Hamanaka et al, 19 they found that a wider bleb extent and leak showed success in IOP in limbal-based TRAB with no significant results for fornix-based TRAB.…”
Section: Discussionmentioning
confidence: 95%
“…There has been a movement from limbal-based TRAB to a fornix-based TRAB, as the former has a higher risk of developing an avascular bleb with subsequent blebitis than the fornix-based TRAB. 19,27 Unlike TRAB, DS is not entirely dependent on bleb formation. Once aqueous flows across an intact trabeculo-Descemet's membrane, it may enter (i) the open ends of Schlemm's canal; (ii) the intra-scleral space; (iii) the suprachoroidal space; or (iv) the subconjunctival space 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AS-OCT imaging has provided insight into a wide variety of topics including anatomical changes after pupillary dilation and peripheral iridotomy, postsurgical changes after cataract surgery and trabeculectomy, and the relationship between intraocular pressure and the configuration of the anterior chamber angle. 212 …”
mentioning
confidence: 99%